Severe bradycardia and asystole associated with sugammadex: case report - Oliveira,Catarina (2019)
Abstract Background and objectives: Sugamadex is a modified gamma-cyclodextrin, the first selective agent for reversal of neuromuscular blockade induced by steroidal non-depolarizing muscle relaxants, with greater affinity for rocuronium. In this article we present a case of severe bradycardia and asystole following sugammadex administration. Case report: A 54-year-old male patient, ASA II, with a history of hypertension, dyslipidemia and obesity, who underwent an emergency umbilical herniorrhaphy under balanced general anesthesia. Intraoperative muscle relaxation was maintained with rocuronium. At the end of the surgery, the patient maintained a neuromuscular block with two TOF responses, and sugammadex (200 mg) was administered. About thirty seconds after its administration, the patient developed marked bradycardia (HR 30 bpm) followed by asystole. Conclusions: Documented bradycardia and asystole were attributed to the administration of sugammadex. This case shows that, although rare, cardiac arrest is a possible adverse effect of this drug, and that the knowledge of this situation can be determinant for the patient’s evolution.